Flow artifact removal in carotid wall imaging based on black and gray‐blood dual‐contrast images subtraction. Issue 4 (28th March 2016) - Li, Hao; Li, Bo; Huang, Wenjian; Dong, Li; Zhang, Jue
Abstract : Purpose: To develop and validate a dual‐contrast image subtraction (DCIS) strategy for eliminating the flow artifacts in black‐blood carotid MRI. Methods: Twelve patients with carotid stenosis and eight healthy volunteers were imaged using the black and gray‐blood dual‐contrast imaging based on the relaxation‐enhanced compressed sensing three‐dimensional motion‐sensitizing driven equilibrium prepared rapid‐gradient‐echo (RECS‐3D MERGE) sequence. Subtraction of black‐blood images (BBIs) and gray‐blood images (GBIs), together with a preweighting procedure, was performed to eliminate the residual blood signal in BBIs. A wavelet denoising procedure was applied to offset the noise amplification. In addition to the lumen signal‐to‐noise ratio (SNR) and wall‐lumen contrast‐to‐noise ratio (CNR), the signal variance ratio (SVR) and contrast variance ratio (CVR) were also used to evaluate the blood suppression efficiency. Results: By choosing the weighting factor of one, the lumen SNR of DCIS images was approximately 1% of that of the original BBIs, and the CNR showed a 91.4% improvement as compared with the BBIs. The median of the lumen SVR decreased to zero, and the CVR increased to 123% of that of the BBIs. Conclusions: DCIS is demonstrated to be an effective strategy for sufficiently removing the residual flow signal from black‐blood carotid MRI. Magn Reson Med 77:1612–1618, 2017. © 2016 International Society for Magnetic Resonance in Medicine